Answer:
1.2850
Step-by-step explanation:
Using the change of base formula,
Log 10 to base 6 = Log 10 ÷ Log 6
Log 10 = 1
Log 6 = 0.7782
Log 10 ÷ Log 6 = 1 ÷ 0.7782 = 1.2850
I am pretty sure it is 0.064. Hope this helps
Answer:
14.93
Step-by-step explanation:
For this problem you need to know distance formula, which is
d=√(x2-x1)²+(y2-y1)². You'll want to plug in (0,3) and (-2, 9) and go on to plug in all of them at some point. You'll get 6.32 as the distance between (0,3) and (-2, 9), 3.61 as the distance between (-2, 9) and (-4, 6), and 5 as the distance between (-4, 6) and (0, 3). You add them up and get your answer.